Unveiling the predictive synergy of red cell distribution width and peak morning home systolic blood pressure: a dual biomarker approach for cognitive risk stratification in hypertensive minor stroke - Yimin Shu; Jie Chen; Yanjin Song; Wuhong Wang (Frontiers in Neurology)
AimThis study aims to evaluate the predictive value of combining red cell distribution width (RDW) and peak morning home systolic blood pressure (SBP) for post-stroke cognitive impairment (PSCI) in hypertensive patients with minor stroke.MethodsA prospective cohort study enrolled 430 patients, randomly stratified into training (n = 301) and validation (n = 129) cohorts. Multivariable logistic regression and random forest model were employed for analysis.ResultsBoth RDW and peak morning home SBP emerged as independent risk factors for PSCI (OR = 70.95 and 1.104, respectively; p < 0.001 for both). The combined model significantly improved predictive performance, achieving an area under the curve (AUC) of 0.925 (95% CI: 0.901–0.948), surpassing individual biomarkers (RDW: AUC = 0.883; peak morning home SBP: AUC = 0.765). Subgroup analyses demonstrated superior discriminative capacity in coronary heart disease (AUC = 0.956) and female patients (AUC = 0.925).ConclusionThe integration of RDW and peak morning home SBP provides an efficient, cost-effective, and clinically translatable tool for cognitive risk stratification in hypertensive patients with minor stroke, offering enhanced precision over conventional single-biomarker approaches.